Peran Generasi Muda Dalam Membangun Masa Depan Pertanian Indonesia yang Mandiri: The Role of the Young Generation in Building Indonesia's Independent Agricultural Future - Firdausia, Najwa Diah; Rozaki, Zuhud; Wulandari, Retno; Nurlita, Mita (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
Indonesia is a developing country and the main source of income is from the agricultural sector. Agriculture is one of the industries that can improve people's lives by utilizing the economic value of raw materials. The role of the younger generation is becoming increasingly important because it determines the future of the agricultural sector in Indonesia. The agricultural sector has a strategic role in the structure of national economic development, and sustainable development in this sector requires the role of qualified human resources. Indonesia's agriculture is now known to be aging, therefore we want to continue to arouse the interest of the younger generation in agriculture. This generation has access to the latest technology and has the ability to be aware of global trends, so they can contribute to the development of creative solutions to increase the productivity and production capacity of Indonesian agriculture. Farmers must reproduce to maintain food production and discover or develop new technologies in the agricultural sector. The biggest challenge in dealing with the younger generation is to make them realize the importance of agriculture. Human resources are the only resources that have reason, emotion, desire, ability, skill, knowledge, motivation, and effort. Hence the importance of human resources in the agricultural sector. Regeneration has always been a strategic priority, created by previous generations who realized and understood the importance of this.